IMPLEMENTASI NILAI-NILAI KARAKTER MENURUT KEARIFAN LOKAL MASYARAKAT LEMBAK, KECAMATAN BINDURIANG - Lena Lena; Nelson Nelson; Siswanto Siswanto (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
This study aims to find out how the implementation of honest character values, tolerance, social care according to the wisdom of the Lembak community, Lembak Society or also known as the Lembak Tribe which is part of the people of Bengkulu Province, Rejang Lebong Regency. Is a community famous for its local wisdom. attitude of social care, honesty, and tolerance. This research uses a qualitative approach, the data is taken through interviews and observations. Then reduced until a conclusion is drawn. From these results the implementation of honest character values ​​can be seen in the implementation of Rasan Bekulo and also in the implementation of the Pelara Ceremony. While the character of tolerance can be seen in the implementation of Rasan Bekulo and also in the implementation of Sambai / Nandai and social care characters can be seen in the implementation of the death commemoration from death to the hundred daily events. Form of care for the bereaved family by helping both in terms of energy, material, and as much as they help.